Konstruksi Pemikiran Hukum Islam Imam Ahmad Ibn Hanbal: Pendekatan Sejarah Sosial Hukum Islam - Muslim Zainuddin (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2023)
Imam Ahmad Ibn Hanbal was one of the Hanbali mazhab philosophers who lived during the Abbasid dynasty. A number of ideas were followed by scholars after him. Though he suffered various rejections from other scholars and even rulers, Imam Ahmad Ibn Hanbal's thought is still relevant to the development of contemporary Islamic law. This article aims to analyze the influence of Imam Ahmad Ibn Hanbal's thinking in the context of the reformation of Islamic law. Data is obtained through the study of documents using descriptive methods and analyzed critically. The results of the research showed that Ahmad ibn Hanbal's strong tendency towards the hadiths undermined the formulation of hadith-based fikih. The intensity of the use of the hadith and the giving of sufficiently strong authority made Ahmad Ibn Hanbal, in the view of some fuqaha, a fuqaha muhadditsin. One thing that became the best practice in Ahmad Ibn Hanbal's character was his diligence in upholding opinions and not being easily influenced by the will of the ruler. This fact can be a reference to the society and the rulers that exist at this time.